Basolateral CD147 induces hepatocyte polarity loss by E‐cadherin ubiquitination and degradation in hepatocellular carcinoma progress. Issue 1 (23rd March 2018) - Lu, Meng; Wu, Jiao; Hao, Zhi‐Wei; Shang, Yu‐Kui; Xu, Jing; Nan, Gang; Li, Xia; Chen, Zhi‐Nan; Bian, Huijie
Abstract : Hepatocytes are epithelial cells with highly specialized polarity. The disorder and loss of hepatocyte polarity leads to a weakness of cell adhesion and connection, the induction of epithelial–mesenchymal transition, and eventually the occurrence of hepatocellular carcinoma (HCC). Cluster of differentiation 147 (CD147), a tumor‐related glycoprotein, promotes epithelial–mesenchymal transition and the invasion of HCC. However, the function of CD147 in hepatocyte depolarization is unknown. Here we identified that CD147 was basolaterally polarized in hepatocyte membrane of liver tissues and HepG2 cells. CD147 not only promoted transforming growth factor‐β1–mediated hepatocyte polarity loss but also directly induced endocytosis and down‐regulation of E‐cadherin which contributed to hepatocyte depolarization. Overexpression of CD147 induced Src activation and subsequently recruited ubiquitin ligase Hakai for E‐cadherin ubiquitination and lysosomal degradation, leading to decreases of partitioning defective 3 expression and β‐catenin nuclear translocation. This signal transduction was initiated by competitive binding of CD147 with integrin β1 that interrupted the interaction between the Arg‐Gly‐Asp motif of fibronectin and integrin β1. The specific antibodies targeting integrin α5 and β1 reversed the decrease of E‐cadherin and partitioning defective 3 levels induced by CD147 overexpression. In human liver tissues, CD147 polarity rates significantly declined from liver cirrhosis (71.4%) to HCC (10.4%). CD147‐polarized localization negatively correlated with Child‐Pugh scores in human liver cirrhosis ( r = –0.6092, P < 0.0001) and positively correlated with differentiation grades in HCC ( r = 0.2060, P = 0.004). HCC patients with CD147‐polarized localization had significantly better overall survival than patients with CD147 nonpolarity ( P = 0.021). Conclusion: The ectopic CD147‐polarized distribution on basolateral membrane promotes hepatocyte depolarization by activation of the CD147–integrin α5β1–E‐cadherin ubiquitination–partitioning defective 3 decrease and β‐catenin translocation signaling cascade, replenishing a molecular pathway in hepatic carcinogenesis. (Hepatology 2018;68:317‐332).